MEMBANGUN MODEL STRATEGI INOVASI PADA KINERJA INDUSTRI MEDIA SIBER DI JAWA TIMUR - Sugiarno, Yuventius (Universitas 17 Agustus 1945 Surabaya, 2021)
Innovation is a case that must be done by business organizations, including the cyber media industry, to improve organizational performance. The increasing intensity of business competition encourages business organizations to carry out sustainable innovation strategies. There are four dimensions of innovation according to the Oslo Manual (OECD, 2005), namely product innovation, innovation process, marketing innovation and organizational innovation. This research is to build an innovation strategy model on the performance of the cyber media industry in East Java by using a product innovation and an innovation process approaches. The method used in this research is qualitative. The sampling technique used was purposive sampling, namely the technique of taking data sources with the consideration that getting an in-depth description of the innovation strategy in the media industry in East Java. The data research technique used in this study was semi-structured interviews (semi-structured interviews) with three informants who had been selected by the researcher. The informants are the leaders of three cyber media industry organizations in East Java. The results showed that the three media carried out an innovation strategy. Product innovation is carried out by adding or developing rubrics on the website of the cyber media subject to this. Meanwhile, the process innovation is carried out by improving services such as interactive communication with 24-hour online readers. In addition, a mix of product innovation and innovation process was carried out by adding services in the form of news broadcasts on the YouTube channel.